Control in Latch-Mediated, Spring-Actuated (LaMSA) systems - Foong, Hui Min (Nanyang Technological University, 2020)
Insects and other small organisms are capable of impressive impulsive motions, producing extraordinarily high forces for their tiny body masses. Jumping is one such motion where these insects achieve high velocities and accelerations, and this jumping behaviour can be replicated via Latch-Mediated Spring-Actuated (LaMSA) mechanisms. However, the ability to control jumping behaviour in engineered systems is currently limited. This paper examines the latch-spring interface as a potential area for control in a small jumping LaMSA robot. Different latch geometries are used to produce varied jumping behaviour across the applied motor voltage range, and a preliminary dynamic analysis of the unlatching process is presented. Deeper understanding of latch dynamics could provide engineers with an alternate approach to designing small robots within system constraints in future. Conventionally, latches are removed from LaMSA systems by an external force or actuator. However, we show that the internal spring force inherent in the system can contribute to the latch removal process, especially in small scale systems where external actuators alone may be weaker. This helps circumvent the limitations of the available low torque motors at this size scale, allowing the jumper design presented in this work to achieve a range of take-off velocities from 1.78m/s to 2.23m/s.